The Effect of Regional Financial Performance on Economic Growth Provinces in Indonesia 2016-2018 Period - Velga Eka Putri; Junaidi (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2020)
The objectives of this study are: (1) to determine the ratio of independence to affect the economic growth of provinces in Indonesia, (2) to determine the ratio of effectiveness affects the economic growth of provinces in Indonesia, and (3) to determine the efficiency ratio affects the economic growth of provinces in Indonesia. This study used a sample of 33 provinces in Indonesia. The sampling technique used cluster samples. The data used are secondary data. The data collection technique uses documentation in the form of reports on the realization of regional income and expenditure budgets and reports on economic growth at constant prices based on the field of business from 2016-2018. The data analysis technique used to answer the hypothesis is multiple linear regression. The results of research that have been conducted state that: (1) the ratio of independence affects the economic growth of provinces in Indonesia, (2) the effectiveness ratio affects the economic growth of the provinces in Indonesia, and (3) the efficiency ratio affects the economic growth of the provinces in Indonesia.